Information and Uncertainty in the Theory of Monetary Policy - Helmut Wagner (SUERF - The European Money and Finance Forum, 2007)
Theory and practice of monetary policy have changed significantly over the past three decades. A very important part of today's monetary policy is management of the expectations of private market participants. Publishing and justifying the central bank's best forecast of inflation, output, and the instrument rate is argued to be the most effective way to manage those expectations.
Keywords: E52; E58; 330; central banks; communication policy; institutional design; uncertainty; microfoundation; Geldpolitik; Information; Politische Kommunikation; Risiko; Theorie